Inter- and Intra-Hemispheric Differences of Non-Linear Dynamics in Electroencephalogram Signals During the Execution of an Attention Test; [Diferencias Inter E Intra-Hemisféricas de Dinámicas No Lineales en Las Señales de Electroencefalograma Durante la Resolución de Una Prueba de Atención] - Diaz-Munoz, H (Universidad Nacional de Colombia, 2020)
Introduction: Considering its aperiodic dynamics, brain activity can be studied by means of non-linear functions or chaotic systems. Objective: To analyze the inter- and intra-hemispheric differences of the order/chaos relationship observed in the beta waves of university students during their participation in an attention test. Materials and methods: The sample was composed of 10 university physical education students, all males, who were administered the Toulouse-Piéron Concentrated Attention Test to record, by means of electroencephalogram, their brain activity for 8 minutes during the execution of the test. The Emotiv Epoc® device was used to record brain activity. Results: Intra- and inter-hemispheric differences were observed in the order/chaos relationship among the participants in the prefrontal, temporal and occipital regions (p<0.05), as well as various correlations between these regions (r>0.600), which varied both between participants and individually as the execution of the test progressed. Conclusion: As the test progressed, hemispheric asymmetries increased, which allows concluding that engaging in continuous cognitive processes causes brain activity differences. However, it is necessary to carry out similar studies in samples with different characteristics (different age groups, women, etc.) in which other attention tests are used to confirm or contrast the results reported here. © 2020, Universidad Nacional de Colombia. All rights reserved.